3D Indoor Surveying – A Low Cost Approach. Issue 353 (4th March 2017) - Kalantari, M.; Nechifor, M.
Abstract : Satisfying the accommodation needs of the world's urban population requires high-rise buildings. Accommodating some of 3.5 billion urban population in complex apartments has created challenges including the human scale understanding of complex 3D property rights, and engineering and architectural features relating to building interiors. Technological developments have brought about the prevalence of inexpensive systems such as gaming consoles and smartphones. This paper explores the use of Kinect for Windows (a consumer grade technology that was originally designed for computer gaming purposes) to survey indoors in 3D. This paper presents the result of an investigation into the utility of this widespread and economical technology for 3D surveying of interiors of buildings in relation to Surveying (Cadastral Survey) Regulation 2005, Victoria, Australia. Building on the results of the investigation, the paper argues that such a technology has the potential to be used in other application domains and crowdsourcing 3D indoor information.